Gerichtsbarkeit im Synedrion: Geschichte einer Institution in Israel ab der hellenistischen Zeit und ihre Entwicklung im Neuen Testament - Paganini, Simone (Zeitschrift für katholische Theologie, 2018)
One of the central issues for groups claiming identity and independence is the administration of justice. In the intertestamental period the Synedrion became the place for adjudicating legal conflicts as, among other functions, a high court. As the Synedrion exerted enormous influence within Judaism, Christian groups comprising more and more of Gentiles became increasingly alienated. The Acts of the Apostles traces this alienation already to the Jerusalem church and ends the description of the community in Jerusalem with the establishment of judicial proceedings with the community itself while at the same time delegitimising the Jewish Synedrion.